Examination of Designed Materials in Digital Environment on Concept Teaching in Special Education. Issue 5 (3rd September 2019) - Soykan, Emrah; Gemikonakli, Eser; Kanbul, Sezer
ABSTRACT: The aim of this study is to investigate the effectiveness of digital materials designed for the use of teachers and students in teaching concept skills to students in need of special education. The concept of the long term was included in the study. As a research model, a single-subject research model and a multiple-probe model were used. The participants of the study consisted of 4 students from different disability groups with the appropriate sampling method. In the study, data forms prepared by the researcher were used as data collection tools. According to the data obtained from the data forms, it was observed that 4 students who participated in the study learned the concept in different time intervals by using digital materials. In general terms, it was observed that all of the students learned the long concept, which is the concept to be taught. By using digital materials, it is concluded that students who are in need of special education support students' individual learning skills independently of time and place and this was supported by teachers' opinions.